IVIg-exposure and thromboembolic event risk: findings from the UK Biobank. Issue 8 (10th June 2022) - Kapoor, Mahima; Hunt, Ian; Spillane, Jennifer; Bonnett, Laura Jayne; Hutton, Elspeth Jane; McFadyen, James; Westwood, John-Paul; Lunn, Michael P; Carr, Aisling S; Reilly, Mary M
Abstract : Background: Arterial and venous thromboembolic events (TEEs) have been associated with intravenous Ig use, but the risk has been poorly quantified. We aimed to calculate the risk of TEEs associated with exposure to intravenous Ig. Methods: We included participants from UK Biobank recruited over 3 years, data extracted September 2020. The study endpoints were incidence of myocardial infarction, other acute ischaemic heart disease, stroke, pulmonary embolism and other venous embolism and thrombosis. Predictors included known TEE risk factors: age, sex, hypertension, smoking status, type 2 diabetes mellitus, hypercholesterolaemia, cancer and past history of TEE. Intravenous Ig and six other predictors were added in the sensitivity analysis. Information from participants was collected prospectively, while data from linked resources, including death, cancer, hospital admissions and primary care records were collected retrospectively and prospectively. Findings: 14 794 of 502 492 individuals had an incident TEE during the study period. The rate of incident events was threefold higher in those with prior history of TEE (8 .7%) than those without previous history of TEE (3.0%). In the prior TEE category, intravenous Ig exposure was independently associated with increased risk of incident TEE (OR=3.69 (95% CI 1.15 to 11.92), p=0.03) on multivariate analysis. The number needed to harm by exposure to intravenous Ig in those with a history of TEE was 5.8 (95% CI 2.3 to 88.3). Intravenous Ig exposure did not increase risk of TEE in those with no previous history of TEE. Interpretation: Intravenous Ig is associated with increased risk of further TEE in individuals with prior history of an event with one further TEE for every six people exposed. In practice, this will influence how clinicians consent for and manage overall TEE risk on intravenous Ig exposure.